E-modul Literasi Menumbuhkan Karakter Gemar Membaca melalui Aplikasi Flipbook Pada Siswa Sekolah Dasar - Leni, Marselina; Chrisyarani, Denna Delawanti; Setiawan, Dwi Agus (Peneliti.net, 2026)
The purpose of this research is to develop e-modules of literacy education based on Flipbook application to increase reading interest among elementary school students. This research is motivated by the low interest in reading among students and the limited interactive and interesting learning media. The research and development (R&D) method was used with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The test subjects were limited to fifth grade students at one of the Bandungrejosari 3 elementary schools in Malang. Data were collected through observation and questionnaires, and analyzed descriptively quantitatively and qualitatively. The development results show that the flipbook-assisted literacy e-module is effective in fostering students' interest and character in reading in digital literacy learning. Thus, the use of e-modules with flipbooks can be an alternative solution for character-oriented learning.